Stature of young people with malignant bone tumors - Cotterill, Simon J.; Wright, Charlotte M.; Pearce, Mark S.; Craft, Alan W. (Pediatric Blood & Cancer, 2004)
Background Little is known about the aetiology of primary bone tumours. There have been conflicting reports relating to stature in young people with bone cancer. Patients We analysed height data at diagnosis for 364 patients with osteosarcoma and 356 patients with Ewing sarcoma registered on clinical trials run by the Medical Research Council (MRC) and the United Kingdom Children's Cancer Study Group (UKCCSG). Main Outcome Measures Height at diagnosis for each patient was standardised for age and sex compared to national reference data with a standard deviation score (SDS) calculated for each subject. Results Those with osteosarcoma were significantly taller than the general population (mean height SDS 0.2, P = 0.001). Patients with osteosarcoma of the femur were significantly taller than patients with other primary sites (mean height SDS 0.45 vs. −0.06, P = 0.0001). Overall those with Ewing sarcoma were not significantly taller than the general population (mean height SDS 0.09, P = 0.1), but children presenting under 15 years were taller (SDS 0.2, P = 0.004) whilst older patients were not (SDS −0.07, P = 0.4). In both osteosarcoma and Ewing sarcoma the mean age at diagnosis for females was significantly younger than for males. Conclusions This study suggests that tall stature and an earlier pubertal growth spurt may be important factors in the aetiology of both osteosarcoma and Ewing sarcoma. © 2003 Wiley‐Liss, Inc.